Bilateral Relations of Vocational Education and Industry in Work Based Learning Model: Effective or Problematic? - Al Wafi, Raden Rifqi Hafizhuddin (INVOTEC, 2020)
This study shows the background that occurs between industry and vocational schools. The purpose of this study is to uncover the problems that occur in bilateral relations between vocational and industrial secondary education institutions for work-based learning models that have existed before. The method used in this study is a separate analysis by researchers with qualitative methods. The results found factors that inhibit learning do not run effectively because the industry in providing information about the latest technology used by the company is not distributed evenly so that the facilities available in each school are different, the character of student work is not in accordance with the mental needs of the industry, the lack of monitoring of the implementation of the Moment of Understanding that is overseen by a clear legal body / institution, the duration of time given is less effective in the industry because time constraints make students unable to apply the many theories obtained at school.